The role of community leaders in the prevention of prostitution in Eretan Kulon Village: Perspective social structure theory - Ferti Ferti; Antari Ayuning Arsi (Universitas Muhammadiyah Malang, 2025)
The persistence of prostitution in Eretan Kulon Village, Kandanghaur District, Indramayu Regency, is a significant social concern. This study seeks to elucidate the perspectives of the community and the preventive measures undertaken by the community leaders. Employing a qualitative research methodology with a case study approach, this investigation engaged 13 informants, including community leaders, law enforcement officials, and local residents. Thematic analysis was used as the data analysis technique. The findings indicate that the majority of the population perceives prostitution as a negative phenomenon primarily driven by economic factors, although many acknowledge the challenges in eradicating it. Community leaders have implemented various preventive strategies, such as routine raids, educational initiatives, counseling on the adverse effects of prostitution, rehabilitation programs, HIV testing, regular religious gatherings and public demonstrations. While these efforts have not completely eradicated prostitution, there has been a noticeable decline in its practice in the village. Collaboration between the police, Satuan Polisi Pamong Praja, religious leaders, and village governments is pivotal in addressing this issue. This research contributes to the understanding of the role of community leaders and the significance of inter-agency collaboration in addressing prostitution in the village, highlighting that active community participation is essential for effectively tackling this social issue. Praktik prostitusi di Desa Eretan Kulon, Kecamatan Kandanghaur, Kabupaten Indramayu, masih menjadi masalah sosial. Penelitian ini bertujuan untuk mengetahui pandangan masyarakat dan upaya pencegahan yang dilakukan tokoh masyarakat. Menggunakan metode penelitian kualitatif dengan pendekatan studi kasus, penelitian ini melibatkan 13 informan, termasuk tokoh masyarakat, aparat penegak hukum, dan warga setempat. Teknik analisis data yang digunakan adalah analisis tematik. Hasil penelitian menunjukkan mayoritas masyarakat memandang prostitusi sebagai fenomena negatif yang dipengaruhi oleh faktor ekonomi, meskipun sebagian besar menganggapnya sulit dihilangkan. Tokoh masyarakat telah melakukan berbagai upaya pencegahan, seperti razia rutin, pembinaan, penyuluhan dampak negatif prostitusi, program rehabilitasi, pemeriksaan HIV, pengajian rutin, dan unjuk rasa. Meskipun upaya tersebut belum sepenuhnya menghilangkan prostitusi, praktik prostitusi di desa ini telah menunjukkan penurunan. Kolaborasi antara polisi, Satpol PP, tokoh agama, dan pemerintah desa berperan penting dalam mengatasi masalah ini. Penelitian ini memberikan kontribusi dalam memahami peran tokoh masyarakat dan pentingnya kolaborasi antar lembaga dalam menanggulangi prostitusi di desa, serta menunjukkan bahwa partisipasi aktif masyarakat sangat penting untuk keberhasilan penanggulangan masalah sosial ini.